2002
DOI: 10.2337/diacare.25.12.2314
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Induced Decreases in Aortic Wave Reflection and Central Systolic Pressure Are Impaired in Type 2 Diabetes

Abstract: OBJECTIVE -To determine whether large arteries are resistant to insulin.RESEARCH DESIGN AND METHODS -Insulin normally acutely decreases central systolic pressure by decreasing wave reflection in vivo. This effect occurs before any changes in peripheral vascular resistance or heart rate under normoglycemic conditions. We determined whether the ability of insulin to decrease central aortic pressure is altered in uncomplicated type 2 diabetes. The study subjects consisted of 16 type 2 diabetic patients (age 54 Ϯ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…This finding is also consistent with an earlier study showing decrease in AI under the insulin clamp technique, whereas no significant relation between D AI and changes in glucose or insulin levels. 29 These results support the hypothesis that postprandial hemodynamic changes may affect baPWV and AI more directly than the other changes including biochemical, hormonal and autonomic changes.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is also consistent with an earlier study showing decrease in AI under the insulin clamp technique, whereas no significant relation between D AI and changes in glucose or insulin levels. 29 These results support the hypothesis that postprandial hemodynamic changes may affect baPWV and AI more directly than the other changes including biochemical, hormonal and autonomic changes.…”
Section: Discussionsupporting
confidence: 83%
“…Acute administration of insulin has been shown to have vasodilatory effects. In normal men, infusion of physiologic doses of insulin decreases the augmentation index within 1 h, consistent with increased distensibility or vasodilatation of large arteries, whereas the vasodilatory response to insulin in patients with T2DM occurred after 2 h, suggesting that the delayed insulin action due to IR could predispose patients with diabetes to develop systolic hypertension [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance and diabetic status have been shown to be favorably associated with AIx and central BP in observational studies in patients with diabetes mellitus 22,23 and general populations, 9,13 as well as in an experimental study using a euglycemic insulin clamp technique. 24 We also reported that not only increased insulin resistance but also reduced insulin sensitivity assessed by an oral glucose tolerance test were factors that Values are mean±standard deviation.…”
Section: Discussionmentioning
confidence: 99%